THE B-FORM TO Z-FORM TRANSITION OF POLY(DG-M(5)DC) IS SENSITIVE TO NEUTRAL SOLUTES THROUGH AN OSMOTIC-STRESS - Preisler, R. S.; Chen, H. H.; Colombo, M. F.; Choe, Y.; Short, B. J.; Rau, D. C. (Amer Chemical Soc, 1995)
Several neutral solutes, ranging in size from methanol to a tetrasaccharide, stachyose, are shown to stabilize the left-handed Z form of the methylated polynucleotide poly(dG-m(5)dC). The action of these solutes is consistent with an osmotic stress, that is, with their effect on water chemical potentials coupled to a difference in the number of-associated water molecules between the B and Z conformations. The apparent difference in hydration between the two forms is, however, dependent on the particular solute used to probe the reaction. The effect of solutes is not consistent either with a direct binding of solute or with an indirect effect on electrostatics or ion binding through changes in the solution dielectric constant. The interplay of NaCl and neutral solute in modulating the B-Z transition suggests that salt also could be stabilizing the Z form through an osmotic stress.